Evidence of surgical trephinations in infants from the 7th-9th centuries AD burial site of Kiskundorozsma-Kettőshatár - Bereczki, Zsolt (Acta Biologica Szegediensis, 2010)
The authors found 3 infant skulls with cranial lesions in the 7th-9th centuries AD (Avar Age) burial site of Szeged-Kiskundorozsma-Kettôshatár. The remains were examined with standard macromorphological methods of bioarcheology. The most presumable diagnosis of the lesions is surgical trephination. Infants and Avar Age findings were formerly underrepresented in the otherwise abundant and internationally significant amount of paleopathological cases with cranial interventions found in Hungary. Thus, these findings may alter the assumption we formerly had of the cranial surgery of the Avars. During the search for trephined lesions, signs of severe inflammation of the meninges were found in one case and slight hydrocephalus occurred in another implying possible skeletal tuberculosis that put forward interesting questions in connection with healing practices and believes of this era. Together with other Avar Age findings formerly known from the nearby areas these results refine our knowledge of Avar Age medical practices and also the general picture of the medical history of the Carpathian Basin.